Imposition of penalties and occupational accidents in the prefectures of Thessaloniki and Kilkis - Mekos, Konstantinos (SPOUDAI Journal of Economics and Business, 2009)
This article examines the impact of health and safety inspections on companies in the areas of Thessaloniki and Kilkis between 2001 and 2004. The explanatory power of the enforcement model of specific deterrence is evaluated using data on serious injuries and penalties imposed. A unique plant- level dataset is employed and models with panel data are used. The logit fixed effects model is found to be the most appropriate. The conclusion is that certain forms of penalties have an impact on the reduction of workplace accidents, but further research is necessary, especially on the inspections without penalties. JEL Classifications: J28, H11, D73, C23.